Optimizing Growth and Flavonoid Production in Kaempferia angustifolia Using Organic (Chicken and Cow Manure) and Inorganic Fertilizers - Aziz, Sandra Arifin; Ridwan, Taopik; Iswantini, Dyah; Trivadila, Trivadila; Murni, Anggia; Rafi, Mohamad (Department of Agronomy and Horticulture, IPB University, 2025)
Kaempferia angustifolia originated in Southeast Asia and is widely used for its medicinal properties. One of which is from its flavonoids. The research aims to determine the optimal dosage of organic and inorganic fertilizers for promoting the growth and flavonoid production of K. angustifolia. The study was laid out in a split-plot design using organic fertilizers as the main plots (chicken and cow manure at 10 t.ha-1) and inorganic fertilizers as the subplots, consisting of 19 combinations of urea, SP36, and KCl. Each treatment has three replications. The results showed that there is no interaction between organic and inorganic fertilizers in affecting the growth of Kaempferia angustifolia. Plants treated with chicken manure at 10 tons per hectare have a higher fresh weight than those treated with cow manure. Plants without inorganic fertilizer application showed suppressed growth and yielded more rhizomes three months after planting. Inorganic fertilizer promoted more shoots and tillers, with the highest value obtained from 100 kg.ha-1 urea + 200 kg.ha-1 SP36 + 200 kg.ha-1 KCl application. The range of total flavonoids in inorganic fertilizer applications is 39.30-131.51% higher than the control, with the highest value observed at 200 kg.ha-1 SP36 + 200 kg.ha-1 KCl application. The results of this study would be useful for producing K. angustifolia for the medicinal industry, using either organic or inorganic fertilizers.